Design and Implementation of a Web-Based Application for Media and Laboratory Reagents Management with QR Code Feature - Kuwandari, Fira; Susanti, Rahmi; Grey, Michael Alfian; Inderiati, Dewi (Jurusan Teknik Elektromedik, Politeknik Kesehatan Kemenkes Surabaya, Indonesia, 2023)
Planning needs, purchasing, determining the availability of practical materials, and keeping an eye on the state of the actual or real amount are the first steps in practical material management operations. This task is completed to ensure the accuracy of the bookkeeping records in order to reduce variations in inventory levels. The goal of the study is to manage media practice materials and QR Code-based laboratory reagents as efficiently as possible. In this study using the Waterfall method which is included in the SDLC (Software Development Life Cycle) model. The laboratory equipment inventory application is made using a sublime text editor and uses PHP, HTML, CSS programming languages and bootstrap frameworks to make the application look more attractive. The system's use demonstrates the efficiency and precision with which data on laboratory equipment is recorded in order for the leadership to make decisions regarding the proper quantity of teaching and learning aids to be purchased. The unique feature of this system is the direct smartphone connection of the notification, which makes it simpler for users to keep track of inventory flow. The inventory service notification system through WhatsApp is expected to contribute to improving the quality of academic services and meeting the needs of its users. From the results of this study states that the application design used can be a solution in overcoming previous problems so as to achieve effective and efficient data collection activities.